Mulheres e o consumo sustentável : percepções e desafios no contexto do Instituto Federal de Educação, Ciência e Tecnologia de Sergipe - IFS - Siqueira, Rosana Rocha (2015)
The motivation for the accomplishment of this study arose from the perception of problems that pervade the conflicted field related to women and consumption practices, in front of the increasing appreciation of consumption practices in contemporary times, it´s possible to realize inseparable aspects of the economic sphere, environmental, cultural and symbolic beyond the handling of so-called |hegemonic forces| of goods production and new needs. The border between empowerment and the consumption has become increasingly tenuous, since marketing approaches connected the sense of freedom of choice for consumers to exercise citizenship. This research aims to analyze the perceptions of women in relation to their consumption practices in the light of the concept of sustainable consumption. As site of the research was elected Federal Institute of Education, Science and Technology from Sergipe on campuses Lagarto, Itabaiana, Estância, São Cristóvão, Aracaju, Nossa Senhora da Glória and Rectory, where women servants were covered (teachers and TAEs ) and participants of the Thousand Women program. This is an explanatory, qualitative and quantitative research whose research facilities are based on perception and phenomenological approach proposed by Alfred Schutz. For the organization and categorization of the responses obtained in the questionnaires was chosen content analysis, according to Bardin (1977). The contribution of the study to environmental sciences lies in the production of new knowledge that can converge with the advancement of science guided in the interdisciplinary dialogue in the consumer issues, especially in the Northeast region of the country. The data show that consumption appears as a way to improve the living conditions and |reward| the efforts made through the work, whether formal or informal. Thus, the perceived still not realized fully in the lived of these women, because some obstacles such as lack of information on sustainable consumption, lack of selective collection options, cooking and other actions oil collection still hinder effective participation and continuous, since of public policies related to sustainable consumption, which are unknown to most women.